UMMA KALADA SEBAGAI RUANG SAKRAL DAN MEDIA PENDIDIKAN MORAL SUKU KALINDAKANA WEELEWO KATODALOBO SUMBA BARAT DAYA MENURUT PEMIKIRAN MIRCEA ELIADE - Mathias Adon; Martinus Renda (Harmoni, 2022)
This research focuses on exploring the meaning of umma kalada religiosity as a sacred space for the Kalindakana Weelewo Katodalobo Sumba Barat Daya tribe in the light of Mircea Eliade's thoughts. This study aims to make the concept of the umma kalada sacred space a moral education medium. This research was born from the author's awareness that umma kalada is not only a traditional house but also has high religious meaning and value so that it can direct the Kalindakana Weelewo Katodalobo tribe to achieve the fullness of life as civilized human beings in their relationships with others, nature and with the Holy One. This research used the interview and observation methods of the umma kalada, Kalindakana Weelewo Katodalobo, Southwest Sumba, NTT from 17-21 September 2021 as well as a literature study in the light of Mircea Eliade's thoughts. In other words, The concept of sacred space in Mircea Eliade's thought becomes a framework for understanding the concept of umma kalada religiosity. Therefore, exploring the concept of the sacred space of umma kalada in the light of Mircea Eliade's thoughts can help to understand the concept of religiosity of the Kalindakana Weelewo Katodalobo tribe and can be used as a medium for moral education. So this research emphasizes the importance of appreciating and exploring the religious traditions of ethnic groups because each religious tradition has beautiful character and wisdom values about how living together is regulated and preserved.